Bürger als politische Akteure. Überlegungen zur allgemeinen Politikkompetenz bei Platon und Aristoteles - Manuwald, Bernd (Hyperboreus, 2015)
In recent years intensive discussions on the signiﬁcance of key competencies for the development of individuals and society as a whole have led to a differentiation between distinct areas of competencies, as can be seen in the results of the DeSeCo project run by the OECD. Therefore some scholars of pedagogy have raised the question of whether one should also look into a general competency in politics, as a kind of meta-competency, such as ‘public spirit’. That this difﬁcult question, which goes to the heart of every democratic constitution, is not new is demonstrated by similar considerations in Plato’s Protagoras and Aristotle’s Politics: as a detailed analysis shows, these two texts provide different answers to this question. While the dialogue’s Protagoras argues that all Athenians could be educated politically by means of training from an early age onwards, be it by living in a society, be it by being taught by teachers like himself, he cannot prove, in the face of Socrates’ criticism, that this does not merely lead to the required social behaviour, but also yields competencies for political activity. Aristotle considers the political involvement of the entire populace in particular decisions as justiﬁed (since the scattered, limited faculties of individuals add up), but he believes that the best form of democracy is ensured when leading positions are not available to everyone; and he argues that the involvement of all citizens can only function under particular conditions, including a legal framework and a sufﬁcient level of education. Thus both texts point to limitations; this indicates the complexity of this problem, which has remained difﬁcult to solve until the present day.